Enhancing L2 learning through a mobile assisted spaced-repetition tool: an effective but bitter pill?. Issue 1 (2nd January 2020) - Seibert Hanson, Aroline E.; Brown, Christina M.
Abstract: We tested the effectiveness of the spaced-repetition flashcard application, Anki, on improving 62 university-level learners' second language (L2) learning in a semester-long beginning Spanish course. Using effective study strategies is critical for L2 learning, but college students learning an L2 often study with strategies that are only useful for short-term performance. Prior research has shown that spaced-repetition testing increases long-term memory retention so we hypothesized that regularly studying L2 vocabulary with Anki would improve L2 learning. Participants were students enrolled in a beginning Spanish course who were assigned to study with Anki as a class requirement. The results showed a positive relationship between days studying with Anki and Spanish performance at the end of the semester even while controlling for baseline abilities and for motivation, self-efficacy, and beliefs. However, students were reluctant to use the app and reported low enjoyment. Regardless, participants also reported having higher motivation and more effort-based or incremental beliefs about learning at the end of the semester. The present study answers calls for experimental research on specific strategy interventions that also produce genuine gains in second language acquisition.